Optimizing nodulation and pod yield in french bean through strategic molybdenum supplementation - Bhasker, Pattipaka; Suresh, Gali; Keerthi, Pattam; Kundu, Preeti; Janaagal, Monika; Kumar , Vijay; Rani, Pooja (Bangladesh Journal of Botany, 2025)
A field experiment was conducted to evaluate the effect of molybdenum (Mo) on the nodulation, growth and yield performance of French bean (Phaseolus vulgaris L.). Mo supplementation significantly enhanced nodule formation, size and dry matter accumulation, which in turn improved biological nitrogen fixation. This physiological improvement was further supported by an increase in photosynthetic pigment content, indicating higher photosynthetic efficiency. Consequently, Mo treated plants exhibited superior growth characteristics, including increased plant height (45.53 cm), a greater number of branches (5.33 per plant), higher nodule count (25.20 per plant), and greater dry matter accumulation (3.99 g per plant). Improved nodulation with Mo application positively influenced photosynthetic pigments, growth and yield attributes, ultimately leading to higher pod productivity. Among the different Mo treatments, the most effective method involved soil drenching of Mo at the root zone followed by foliar applications. This combination significantly enhanced nodulation, growth and yield-related attributes. The findings underscore the importance of Mo application, particularly through a combined soil drench and foliar spray strategy in improving the growth and productivity of French bean. Bangladesh J. Bot. 54(4): 1021-1026, 2025 (December)